A Rare Case of Acute Pancreatitis Due to Very Severe Hypertriglyceridemia (>10 000 mg/dL) Successfully Resolved With Insulin Therapy Alone: A Case Report and Literature Review. (August 2018) - Gayam, Vijay; Mandal, Amrendra Kumar; Gill, Arshpal; Khalid, Mazin; Sangha, Ruby; Khalid, Mowyad; Garlapati, Pavani; Bhattarai, Bikash
A 48-year-old male presented to the psychiatric emergency room for dysmorphic mood. He was admitted to medical service for the management of hyponatremia, which was discovered in his initial laboratory workup. After the first day of admission, he developed abdominal pain and fever, and subsequent laboratory work revealed a triglyceride level of 10 612 mg/dL (reference range = 0-194 mg/dL). Computed tomography scan of the abdomen and pelvis revealed a hypodense lesion in the pancreas surrounded by a moderate amount of peripancreatic fluid suggestive of hemorrhagic pancreatitis. Based on the laboratory findings and imaging, we diagnosed acute pancreatitis (AP) secondary to hypertriglyceridemia. The patient was initiated on intravenous fluids and insulin to help decrease the triglyceride level with the plan to initiate apheresis. However, the patient improved on insulin therapy alone, which negated the need for apheresis, and the patient was discharged with fenofibrate with no further complications. While elevated triglycerides are a well-known cause of AP, we sought to assess various treatment options in management, especially considering a severely elevated triglyceride level of >10 000 mg/dL. Along with supportive care in AP, there are additional options in hypertriglyceridemia AP, including heparin, insulin, apheresis, antioxidants, and fibrates. Currently, there are no clear guidelines favoring one therapeutic option over the other.